2019
DOI: 10.1001/jamapediatrics.2019.0025
|View full text |Cite
|
Sign up to set email alerts
|

Association of Atopic Dermatitis With Sleep Quality in Children

Abstract: Key Points Question Do children with atopic dermatitis experience impaired sleep duration and sleep quality throughout childhood, and do disease severity and activity affect their sleep? Findings In this longitudinal cohort study of 13 988 children, atopic dermatitis was statistically significantly associated with impaired sleep quality but not sleep duration throughout childhood. Sleep impairment was more common among children with more severe disease and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
122
1
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 168 publications
(138 citation statements)
references
References 57 publications
3
122
1
6
Order By: Relevance
“…Sleep quality in patients with AD has been evaluated by various subjective tools. Silverberg et al examined sleep disturbance in patients with AD by a cross-sectional questionnaire of 34,613 adults and reported that eczema was associated with fatigue [odds ratio (OD), 2.97], regular daytime sleepiness (OD, 2.66), and regular insomnia (OD, 2.36) [16], roughly in line with a study reported by Li et al in which sleep were detected in 15-65% of children with AD, although total sleep duration was similar between children with active AD and without AD [18]. Thus, the previous studies demonstrated that AD definitely impairs subjective sleep quality.…”
Section: Discussionsupporting
confidence: 86%
“…Sleep quality in patients with AD has been evaluated by various subjective tools. Silverberg et al examined sleep disturbance in patients with AD by a cross-sectional questionnaire of 34,613 adults and reported that eczema was associated with fatigue [odds ratio (OD), 2.97], regular daytime sleepiness (OD, 2.66), and regular insomnia (OD, 2.36) [16], roughly in line with a study reported by Li et al in which sleep were detected in 15-65% of children with AD, although total sleep duration was similar between children with active AD and without AD [18]. Thus, the previous studies demonstrated that AD definitely impairs subjective sleep quality.…”
Section: Discussionsupporting
confidence: 86%
“…For example, Kong, Han, Lee, and Son [25] found that the severity of atopic dermatitis (assessed using the scoring atopic dermatitis scale) and sleep quality (assessed using the children's sleep habits questionnaire) demonstrated significant correlations. Recently, a longitudinal cohort study also found that total sleep duration was similar between children with and without atopic dermatitis; however, children with atopic dermatitis had significantly worse sleep quality from 1 to 16 years of age [26].…”
Section: Discussionmentioning
confidence: 96%
“…Eczema and related symptoms such as chronic itchiness, red patchy skin appearance and disturbed sleep could negatively affect mental health via social isolation, low self-image, lack of concentration and more irritability, and possibly also via low-grade inflammation and blood-brain barrier disruption. 10,[24][25][26] Conversely, stress, as a proxy of these problems, could shift the balance towards type 2 T helper cells via the hypothalamic-pituitary-adrenal axis and sympathetic adrenomedullary system, leading to more susceptibility to atopic inflammation and diseases, resulting in a vicious cycle. 7 Another explanation is based on shared pathogenesis between eczema and mental health disorders, as both skin cells and neurons originate from the ectoderm.…”
Section: Discussionmentioning
confidence: 99%